From Crisis to Recovery: Successful Experiences in the Eradication of Narcotics in Afghanistan Local Communities - Fayaz Gul Mazloum Yar (PT. Publikasiku Academic Solution, 2024)
Afghanistan, as one of the world’s largest producers of narcotics, faces significant social, economic, and health challenges. Despite numerous efforts to combat the cultivation and consumption of narcotics, the issue remains a major problem in many local communities. However, some of these communities have succeeded in achieving remarkable progress in reducing narcotics cultivation and consumption through participatory programs and alternative economic development. This research aims to identify and analyze the successful experiences in narcotics eradication in local Afghan communities and to evaluate the factors contributing to these successes. A qualitative methodology was employed, utilizing semi-structured interviews with local community members, experts, and government officials. The data were analyzed using qualitative content analysis. The findings of the research indicate that educational programs, awareness-raising initiatives, the development of alternative economic opportunities, and active community participation have played a crucial role in reducing narcotics cultivation and consumption. Nevertheless, challenges such as financial constraints, administrative corruption, and cultural resistance remain significant barriers to the successful implementation of these programs. The study concludes that with increased international support, administrative transparency, and strengthened educational and economic programs, the dependency of local communities on narcotics cultivation can be significantly reduced. This research provides a foundation for the development of effective national policies in the fight against narcotics in Afghanistan.